An experimental study of deformation and fracture characteristics of shale with pore-water pressure and under triaxial cyclic loading. Issue 8 (22nd August 2018) - Jiang, Changbao; Lu, Tianyu; Zhang, Dongming; Li, Guangzhi; Duan, Minke; Chen, Yufei; Liu, Chaosheng
Abstract : The deformation and fracture characteristics of shale in the Changning-Xingwen region were experimentally studied under triaxial cyclic loading with a controlled pore-water pressure. An RLW-2000M microcomputer-controlled coal-rock rheometer was used in the State key Laboratory of coal mine disaster dynamics and control in Chongqing University. These experimental results have indicated the following. (i) The shale softened after being saturated with water, while its failure strength decreased with the increase of axial strain. (ii) A complete cyclic loading–unloading process can be divided into four stages under the coupling action of axial cyclic loading and pore-water pressure; namely the slow or accelerated increasing of strain in the loading stage, and the slow or accelerated decreasing of strain in the unloading stage. (iii) The axial plastic deformation characteristics were similar when pore-water pressures were set to 2, 6 and 10 MPa. Nevertheless, the shale softened ostensibly and fatigue damage occurred during the circulation process when the pore-water pressure was set to 14 MPa. (iv) It has been observed that the mean strain and strain amplitude under axial cyclic are positively correlated with pore-water pressure, while the elastic modulus is negatively correlated with pore-water pressure. As the cycle progresses, the trends in these parameters vary, which indicates that the deformation and elastic characteristics of shale are controlled by pore-water pressure and cyclic loading conditions. (v) Evidenced via triaxial compression tests, it was predominantly shear failure that occurred in the shale specimens. In addition, axial cyclic loading caused the shale to generate complex secondary fractures, resulting in the specimens cracking along the bedding plane due to the effect of pore-water pressure. This study provides valuable insight into the understanding of the deformation and failure mechanisms of shale under complicated stress conditions.